A Novel Switched-Capacitor Enhanced-Boost Quasi Z-Source Network (2023)
This paper presents a novel switched-capacitor enhanced-boost quasi-Z-source inverter (SCEB-qZSI) for renewable energy applications. The described topology is a novel power electronic converter that uses switched-capacitors to increase the voltage boost. In the meanwhile, a reduced shoot-through condition results in a higher dc-link voltage. Moreover, the proposed concept has the advantages of continuous input current, smaller current ripple, common grounding, and high output voltage gain. The proposed topology is thoroughly examined, and simulation data are used to support the theoretical analysis. The proposed SCEB-qZSI topology has potential uses in electric vehicles, industrial applications, and renewable energy systems which may develop by using the inexpensive components making it an attractive option for applications that have limited funds. D represents the shoot-through duty ratio of the inverter switches which can range from 0<D<0.144. In the proposed topology inductor voltages, inductor currents, capacitor voltages, diode currents, and voltage source inverter outputs are extracted with and without filters and are discussed in brief. The theoretical and simulation evaluation for the above findings is presented in this paper.